The perspective of fish venom: An overview of the physiology, evolution, molecular and genetics - Brighton Ndandala, Charles; Mustapha, Umar Farouk; Wang, Yaorong; Assan, Daniel; Zhao, Guangwen; Huang, Chunren; Mkuye, Robert; Huang, Hai; Li, Guangli; Chen, Huapu (Frontiers in Marine Science, 2023)
Fish venom has several biological activities, including enzyme activity, cytotoxicity, neurotoxicity, muscular toxicity, haemolytic, and cardiotoxicity, when they enter other species or a human being, they disrupt the physiological systems. Transcriptomic analysis of the fish venom glands revealed a large number of proteins relevant to the pharmacological activity even though they are not well-studied. The limitations in studying fish venoms also have an impact on their molecular characterization. This is partly because of the nature of fish venoms, as they are extremely unstable at normal ambient temperatures making them difficult to study. Venomous fish inhabit both marine and freshwater environments, they have specialized venom-delivery apparatuses. Venom delivery systems have evolved in a various animal species, originally for different purposes including defense, competition, as well as predation. In coastal areas, fish stings are a major problem because they have a serious toxic effect on fishermen, local communities, and visitors. In this study, we have discussed the general perspective of fish venom from marine and freshwater species in different aspects basically in their molecular evolution, physiology, diversity, transcriptome, and proteomic studies. We expect that this paper will provide readers with a unique perspective on understanding the current status of fish venom research as well as working for future studies. Therefore, the gap of knowledge acquired from this study will play as a baseline for researchers discovering new studies and using fish venom in a broader range of biomedical applications, and their biological information that can be used to develop drugs for pharmaceutical uses.